How Effective is Regional Spatial Detail Plans as Instrument of Flood Management (Case Study:Kedurus Watershed,Surabaya City) - Lukman Yusuf; Adjie Pamungkas; Eko Budi Santoso (Institut Teknologi Sepuluh Nopember, 2020)
Surabaya city has detailed spatial planning documents as instruments for flood reduction. The detailed spatial plan for the area regulates land use plans to prevent uncontrolled land use changes that cause flooding. The research question is